Risk decomposition (and risk budgeting) - MacQueen, Jason (Henry Stewart Talks, 2007)
The standard method of decomposing portfolio risk into contributions from individual assets, 'Risk budgeting' by pension funds, Unfortunately, while this analysis gives a unique answer for absolute risk, it gives three very different answers for tracking error, or risk relative to some benchmark (such as the pension fund's liabilities), Description of what is happening, Analysis used by most practitioners does not give the most useful answer
Archived at 2022/04/04